PENGARUH VOLUME PERDAGANGAN SAHAM, LEVERAGE, DAN DIVIDEND PAYOUT RATIO PADA VOLATILITAS HARGA SAHAM - Priana, I Wayan Korin; RM, Ketut Muliartha (E-Jurnal Akuntansi; Vol 20 No 1 (2017)DO - 10.24843/EJA.2017.v20.i01.p01, 2017)
The volatility of stock prices reflects the risks and opportunities that can be obtained by investors. Investors need to pay attention to indicators in technical analysis that will affect stock price volatility such as: stock trading volume, leverage and dividend payout ratio. Stock trading volume describes the condition of securities traded in the capital market that can impact on stock prices. Leverage ratio is used to measure the extent to which the company's ability to meet all its obligations. Dividend payouts can be a benchmark for predicting corporate growth and investment opportunities for investors, so firms with high cash dividends will have lower volatility in stock prices. This study aims to determine the effect of stock trading volume, leverage and dividend payout ratio on stock price volatility. This research was conducted at Indonesia Stock Exchange by selecting the sample of companies that successively included in LQ 45 index in the period of 2013-2015. Population in this research as many as 45 companies and the number of samples selected 13 companies with purposive sampling method, so the number of samples for 3 years to 18 samples. Hypothesis testing method using t test with 5% significance level. The result of hypothesis testing shows that stock trading volume has negative effect on stock price volatility, leverage is negative and significant on stock price volatility and dividend payout ratio have positive effect on stock price volatility.